Successful simultaneous ipsilateral stenting of common iliac artery stenosis and transfemoral aortic valve replacement - Abdullah Nabi Aslan; Hacı Ahmet Kasapkara; Serkan Sivri; Murat Can Güney; Engin Bozkurt (KARE Publishing, 2017)
Summary- Transcatheter aortic valve replacement (TAVR) was designed to treat elderly patients with severe aortic stenosis at high risk for surgery, and is most commonly performed with retrograde approach through femoral arteries. However, in up to 30% of cases, it is either not possible to use this access route or it is considered to have high risk of vascular injury. Alternative approaches have been described for patients with no suitable femoral access: trans-subclavian, transaortic, or direct aortic access; however, since the introduction of new valves deployed with low-profile delivery systems, another alternative transcatheter approach has been discovered. Presently described is experience in 2 cases in which patients were treated with transfemoral TAVR using Edwards SAPIEN 3 transcatheter heart valves immediately following ipsilateral common iliac artery stenting.